Psychometric properties of questionnaires of attitudes of medical students towards research and scientific reading - Romaní-Romaní, Franco (2023)
Introduction. Instruments in Spanish with known psychometric properties are required to measure the attitudes of medical students towards scientific activities. Objectives. To determine the psychometric properties of three instruments to measure attitudes towards scientific research, perceptions about barriers to research and attitudes towards scientific reading. Methods. A cross-sectional study was performed in 311 medical students from an university in Peru. The instruments used the Likert scale of six responses. A confirmatory analysis was performed by modeling structural structures. Results. The instrument on attitudes towards scientific research resulted in three factors, the first (9 items, coefficient α = 0.888), the second (8 items, α = 0.847) and the third (3 items, α = 0.653). Perceptions of barriers to research are evaluated with two factors, one with 6 items (α = 0.779) and the other with 4 items (α = 0.771). The instrument that measure attitudes towards scientific literature has two factors: the first measures expectancy values (8 items, α =0.848) and the second measures self-perceived competences in scientific reading (4 items, α = 0.838). Conclusions. Three differentiated instruments applicable to medical students are presented. These have an established factorial structure and adequate internal reliability for the measurement of attitudes towards scientific research, barriers to research and towards the scientific literature.